JÂWÎ REFERENCE IN ISLAMIC LAW COMPILATION: An Introduction to al-Qawânîn al-Syar‘iyyah by Sayyid Usman - Harahap, Radinal Mukhtar; Syarif, Fajar (UIN Sumatera Utara, 2020)
Abstract: This study describes the construction process that occured in the formulation of Islamic law in the form of Islamic Law Compilation (Kompilasi Hukum Islam/KHI) by recognizing the use of jâwî reference, namely al-Qawânîn al-Syar‘iyyah by Sayyid Usman. This study focuses on answering two questions, i.e. how was the position of this compilation as a guide for judges in the late 19th and early 20th centuries, and what was the content of the law in it? Based on content-analysis approached by the social history of Islamic law, the writers find that the construction can be seen from the position of the jâwî reference as a guideline for Religious Court judges apart from being preserver of jâwî writings from the ulama in Archipelago, as well as affirming the robustness of the madhhab Shâfi‘î as the majority in Indonesian. The construction can also be seen from its content which discusses the needs of the community at that time for the order of Islamic law in Indonesia-as well as its structure in the form of legal material sourced from authoritative books which must also be put forward without denying the praiseworthy customs of the country or the strictness of local wisdom. Keywords: Al-Qawânîn al-Syar‘iyyah, Islamic law, history